Penguatan Kapasitas Santri dalam Membaca Qur’an melalui Riwayat Warsy di Pesantren Al-Falahiyah Batangharjo Lampung Timur - Muhammad Nur Amin; Hasyim As’ari; Kholifatul Muthoharoh; Ahmad Zarnuji; Isnaini Nur Azizah (CV. Creative Tugu Pena, 2022)
An assistance of reading Al-Quran was a crucial activity. This activity was one of the indicators achievement of service, namely understanding of reading al qur’an. This article gave an asisstance of strengthening Santri in reading Qur'an through Warsy History at the Pesantren Al-Falahiyah Batangharjo East Lampung. The service community used Service Learning (SL) method. It was as a medium for integrating voluntary community services with active reflection which is expected to enrich and strengthen training materials in community development with the use of existing assets and potential. Collecting data used interview, observation and documentation. The sample was 60 participants. The result showed that the capacity of students and the knowledge of the Qur'an in society towards the study of qira'at science was understood by students. Then, it gave solution for community towards the recitation of the Qur'an other than qira'at hafs. Keywords: Strengthening Reading Qur’an, Warsy History, Assistance Reading Qur’an